1995
DOI: 10.1007/s001250050340
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and hepatic insulin sensitivity in subjects with impaired glucose tolerance

Abstract: Recent evidence suggests that the postprandial hyperglycaemia in impaired glucose tolerance is primarily due to impaired suppression of basal hepatic glucose output. This in turn appears to be secondary to decreased first phase insulin secretion, although decreased hepatic insulin sensitivity, which is a feature of non-insulin-dependent diabetes mellitus, might also play a role. Eight mildly overweight subjects with impaired glucose tolerance and eight closely matched control subjects with normal glucose toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…This has also been found in previous reports from our group and from others (2)(3)(4)(5)(6)(7)(8)(15)(16)(17). At the same time, these subjects were obese and showed a diminished tissue insulin sensitivity compared with control subjects (NFG/NGT), as previously reported from studies in other IGT subjects (18). However, since ANOVA showed that the difference in tissue insulin sensitivity disappeared when gender, age, BMI, and WHR were used, it follows that the Data are mean Ϯ SEM, expressed as percentage of expected.…”
Section: Discussionsupporting
confidence: 91%
“…This has also been found in previous reports from our group and from others (2)(3)(4)(5)(6)(7)(8)(15)(16)(17). At the same time, these subjects were obese and showed a diminished tissue insulin sensitivity compared with control subjects (NFG/NGT), as previously reported from studies in other IGT subjects (18). However, since ANOVA showed that the difference in tissue insulin sensitivity disappeared when gender, age, BMI, and WHR were used, it follows that the Data are mean Ϯ SEM, expressed as percentage of expected.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we have previously shown that EGP during glucose loading is proportional to fasting EGP, both in non-diabetic and Type 2 diabetic subjects [41,42]. These findings stand in contrast to the conclusion reached by another study [5], in which IGT subjects had normal hepatic sensitivity to insulin. This conclusion, however, was based on the finding of similarly suppressed EGP during a euglycaemic clamp using exogenous insulin infusion rates (equivalent to those used in this study) which are maximally suppressive for EGP and, therefore, cannot detect differences in EGP.…”
Section: Discussioncontrasting
confidence: 63%
“…In studies using graded glucose infusions and the C-peptide deconvolution technique to reconstruct insulin secretory rates, one study [14] documented a slower rise in insulin secretion as a function of rising plasma glucose concentrations in IGT subjects in comparison with subjects with normal gluImpaired glucose tolerance (IGT) is a condition of high risk for the development of Type 2 diabetes. Early physiological studies consistently showed that IGT is an insulin-resistant state [1,2,3,4,5] and documented the presence of impaired insulin response to intravenous glucose [6,7,8,9,10,11]. The general cose tolerance.…”
mentioning
confidence: 99%
“…Various studies have shown that many of these subjects are overweight, and that they are moderately insulin-resistant (Reaven et al, 1989;Berrish et al, 1995). Early studies have already demonstrated increased plasma insulin levels after an OGTT in IGT subjects (Reaven et al, 1989).…”
Section: Impaired Glucose Tolerancementioning
confidence: 99%
“…Various studies have addressed the acute insulin release seen after ivGTT, which have shown decreased (Davies et al, 1994;Ahren and Pacini, 1997) normal (Berrish et al, 1995), increased (Walker et al, 1997) or disturbed first phase release (Lillioja et al, 1988;Byrne et al, 1996). Again, matching for obesity (and age) is important for the interpretation of these results (Kahn et al, 2001).…”
Section: Impaired Glucose Tolerancementioning
confidence: 99%